A tomada de decisão na inovação e competitividade da agroindústria orizícola - Lhamby, Andressa Rocha (2024)
Brazil is considered a leading nation in the global agribusiness scene, thanks to its fertile soil conditions, diverse climates, water abundance, and its role in the production and export of products (FGV, 2019). Over the past 40 years, it has developed in such a way that it will be the main food supplier in the future (CNA, 2020). In this context, rice is the second most cultivated cereal globally, covering an area of approximately 163 million hectares and showing good production potential. Thus, it is reasonable to assume that rice cultivation and its processing into a single consumable product require initiatives that drive the rice industry to meet new challenges. In the meantime, such provocations should, through innovation, differentiation, value addition, and consumption incentives, boost competitiveness using the same raw material, with an eye towards consumer needs. In pursuit of a solution to the problem presented, the aim of this research is to develop a diagnostic that aids in the decision making process in agribusinesses of the rice sector. This study was based on three systematic literature reviews, directed towards developing a decision-making analysis for rice agribusinesses. A questionnaire was developed based on these reviews, distributed electronically, and followed by direct communication, with responses analyzed using advanced statistical tools. The results revealed the interdependence between productivity, people management, and socioeconomic and environmental aspects, identifying that factor such as productivity, people management, and environmental responsibility are crucial for the competitiveness of rice agribusinesses. Additionally, a significant correlation between employee training and effective financial management was found, driving the operational and financial performance of companies, which are essential to sustain growth, promote innovations, and effectively respond to global market challenges.